A PERSPECTIVA SOBRE O ERRO DOS ALUNOS DE PROFESSORES DE MATEMÁTICA DA RECUPERAÇÃO INTENSIVA: ALGUMAS CONSIDERAÇÕES - Ana Cristina da Silva Ambrosio (Universidade do Oeste Paulista, 2015)
The aim of this paper is to present and analyze the vision that mathematics teachers of Intensive Recovery classes have about the mistakes of their students. Data were collected in semistructured interviews with such teachers, held in December 2012 and February 2013. In theory, we assume that the error is inherent in the process of learning, an indicator of what the student knows and how he understands certain content and is an important tool for the teacher analyze it and thus rethink their teaching practice, hence the importance of vision that teachers have about the error. The results showed that, with one exception, the teachers do not understand the error as part of the process of learning and consider it a sign that the student has learned.